Analysis of Customer Relationship Management Strategy in Increasing Interaction and Pension Administration Services - Anandani, Thalia; Atika; Daulay, Aqwa Naser (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
Administration is something that cannot be separated from everyday life. In various contexts, whether in the world of government, business or social organizations, administration has a very important role. This article aims to analyze the Customer Relationship Management (CRM) Strategy in pension administration services and interactions at the Medan VI Regional BKN Office, in improving pension administration interactions and services at the VI Medan Regional State Civil Service Agency (BKN) Office. The research method used is a qualitative method through phenomenology, the data used is primary data which is analyzed through SWOT analysis. The respondents in this study were retirees who had used pension administration services at the BKN Regional VI Medan Office. The implication of this research is the importance of implementing CRM in improving interaction and pension administration services at the BKN Regional VI Medan Office. The results of choosing the right CRM strategy through SWOT analysis. In the I SO Strength Opportunity quadrant, which was selected to improve interaction and retirement administration services at the Medan VI Regional BKN Office, namely by increasing the experience and reputation of retirees, increasing human resources and trained staff, increasing technological progress will digital services, and Increasing partnerships to expand service networks. The results of this research can provide guidance for institutions administering pension administration to optimally utilize CRM technology for better service